Distinct spatial coordinate of visual and vestibular heading signals in macaque FEFsem and MSTd - Lihua Yang (eLife, 2017)
Precise heading estimate requires integration of visual optic flow and vestibular inertial motion originating from distinct spatial coordinates (eye- and head-centered, respectively). To explore whether the two heading signals may share a common reference frame along the hierarchy of cortical stages, we explored two multisensory areas in macaques: the smooth pursuit area of the frontal eye field (FEFsem) closer to the motor side, and the dorsal portion of medial superior temporal area (MSTd) closer to the sensory side. In both areas, vestibular signals are head-centered, whereas visual signals are mainly eye-centered. However, visual signals in FEFsem are more shifted towards the head coordinate compared to MSTd. These results are robust being largely independent on: (1) smooth pursuit eye movement, (2) motion parallax cue, and (3) behavioral context for active heading estimation, indicating that the visual and vestibular heading signals may be represented in distinct spatial coordinate in sensory cortices.